The state of caspian sturgeon stocks in long-term aspect (review of literature) - I. Lepilina N.; T. Vasilieva V.; C. Abdusamadov; И. Лепилина Н.; Т. Васильева В.; А. Абдусамадов С. (South of Russia: ecology, development, 2015)
The paper presents the results of analysis of the state of Caspian sturgeon stocks in long-term aspect. The main factors causing the decline in the state of Caspian sturgeon stocks are considered. It is noted that at the present stage when natural resources of the Volga-Caspian basin have been actively developed by man such factors as human impact and geopolitical changes in the region arise in the general succession of negative factors. It is shown that measures aimed at restoration of these valuable fish populations do not fully solve the problem. В статье приведены результаты анализа состояния запасов осетровых рыб Каспийского моря в многолетнемаспекте. Определены основные факторы, влияющие на снижение состояния запасов каспийских осетровых. Отмечено, что на современном этапе, когда природные ресурсы бассейна Волги и Каспийского моря активно осваиваются человеком, в общей цепи отрицательных факторов появляются такие, как антропогенное влияние и геополитические изменения в регионе. Показано, что мероприятия, направленные на восстановление популяций этих ценных видов рыб, не решают проблему в полной мере.